Implementasi Sensor Proximity Kapasitif Pada Alat Pemberian Pakan Ayam Otomatis - Robi Bagja Nugraha; Yuliarman Saragih; Lela Nurpulaela (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2021)
Farmers still use the conventional system to feed the chickens that are kept. They use their hands to spread the feed on the container and walk along the cage. With such a large cage, of course, it is not easy to carry out periodic supervision quickly on large-scale chicken coops. Based on these problems, therefore we need a tool that is integrated with the Internet of Things used to control and monitor the cage to automatically feed. In order to save time and human effort. Capacitive is a sensor that utilizes the concept of a capacitor, namely storing and releasing charge. This sensor works based on changes in the charge of stored electrical energy due to changes in plate distance, changes in cross-sectional area, and changes in the volumeof the sensor dielectic.